2015
DOI: 10.1371/journal.pone.0116545
|View full text |Cite|
|
Sign up to set email alerts
|

In Vitro Activity of Rifampicin and Verapamil Combination in Multidrug-Resistant Mycobacterium tuberculosis

Abstract: The aim of the present study was to evaluate the effect of the combination of rifampicin (RIF) and verapamil (VP) against the Mycobacterium tuberculosis H37Rv reference strain and six multidrug-resistant (MDR) M. tuberculosis clinical isolates by determining Time-Kill Curves and the ability to efflux drug by fluorometry. The RIF+VP combination showed synergism in one MDR clinical isolate. For the other five MDR clinical isolates, the drug combination showed no interaction. The MDR clinical isolate had lower et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…S2). Verapamil is an efflux pump inhibitor that influences membrane potential (22) and has been previously been shown to potentiate the activity of several anti-TB drugs (2325). In contrast, all pairwise combinations featuring sutezolid were found to be antagonistic.…”
Section: Resultsmentioning
confidence: 99%
“…S2). Verapamil is an efflux pump inhibitor that influences membrane potential (22) and has been previously been shown to potentiate the activity of several anti-TB drugs (2325). In contrast, all pairwise combinations featuring sutezolid were found to be antagonistic.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, combinations containing the drugs chlorpromazine and verapamil were highly enriched for synergistic interactions; 77% of chlorpromazine-containing combinations and 80% of verapamil-containing combinations were found to interact synergistically (FIC < 0.9) ( Figure S2 ). Verapamil is an efflux pump inhibitor that influences membrane potential (22) and has been previously been shown to potentiate the activity of several anti-TB drugs (23-25). In contrast, all pairwise combinations featuring sutezolid were found to be antagonistic.…”
Section: Resultsmentioning
confidence: 99%
“…Multidrug efflux pumps are known to contribute to antibiotic tolerance in M. tuberculosis (38-40). It was reported that after incubation of rifampicin-exposed M. tuberculosis cells in in vitro cultures and in infected macrophages with the efflux pump inhibitor, verapamil, rifampicin levels inside the cells increased thereby enhancing susceptibility (41, 42). This study showed that verapamil-sensitive efflux pump was involved in the removal of rifampicin from the cells.…”
Section: Methodsmentioning
confidence: 99%